Minutes (extract)
016b-0008-001 EXTRACT FROM MINUTES OF NATIONAL COUNCIL OF LABOUR 23rd November 1937 20. Spain: Mr. Gillies reported on behalf of the Spanish Campaign Committee set up by the National Executive Committee of the Party, and indicated that the whole-hearted assistance of the Co-operative Movement had been secured; that the public Demonstrations which had already been held had been highly successful, costs having been covered and substantial collections having been secured for the Fund. The demand for the free leaflets on the Milk Token Scheme had been considerable, and was continuing. It was suggested that arrangements should be made for the preparation of a lay-out illustrating and explaining the scheme for insertion in Trade Union and other journals. Sir Walter Citrine reported upon a meeting of the International Federation of Trade Unions recently held in Paris, when discussion had taken place in regard to the differences that had arisen between various sections of the Spanish Movement. Mr. Attlee reported that he had been invited by Senor Negrin, the Spanish Prime Minister, to visit Spain at an early date, and he proposed to make arrangements accordingly. 292/946/16b/13